EFEKTIVITAS PELATIHAN MENGARANG TERHADAP PENINGKATAN KREATIVITAS VERBAL PADA ANAK USIA SEKOLAH - Sri Muliati Abdullah, Retna Murdaningsih (Jurnal Psikologi, 2011)
This research is aimed to recognize the effect of writing training to enhance the verbal creativity level of school age children. The hypothesis of this research was that, there was the students that followed training had more verbal creativity. There are 25 students of 5thand 6thgrade of SD Sentolo III Yogyakarta assigned to experimental group and 25 students 5thand 6thSD Jlaban Yogyakarta assigned to control group. The experimental design was pretest-postest control group design. The instrument of data measurement was Verbal Creativity Test. The result of independent sample t test indicated that there was a significant difference of verbal creativity score in posttest writing between experimental group and control group, which t = 5,861 (p<0,01). It means that writing training was effective for enhancing the verbal creativity level of school age children especially 5thand 6thgrade students.